KONFLIK BATIN TOKOH UTAMA DALAM NOVEL KIARA KARYA DINNI ADHIAWATY: KAJIAN PSIKOLOGI SASTRA - Mairanda Alfi; Ikhwanuddin Nasution; Nurhayati Harahap (Bahasa Indonesia Prima, 2024)
This research focuses on the Inner Conflict of the Main Character in Kiara's Novel by Dinni Adhiawaty: A Literary Psychology Study. This study aims to describe the forms of inner conflict in the novel Kiara by Dinni Adhiawaty using literary psychology studies. The theory used in this research is Kurt Lewin's theory. The research method used in this research is descriptive-qualitative. The data source used in this research is the novel Kiara by Dinni Adhiawaty, in the form of words and sentences. The results of this study are three forms of inner conflict according to Kurt Lewin's theory: approach-approach conflict, avoidance-avoidance conflict, and approach-avoidance conflict.